2017
DOI: 10.1155/2017/5219418
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Extract Mixture HT042 Improves Bone Growth, Mass, and Microarchitecture in Prepubertal Female Rats: A Microcomputed Tomographic Study

Abstract: Astragalus extract mixture HT042 is a standardized multiherbal mixture comprising Astragalus membranaceus, Eleutherococcus senticosus, and Phlomis umbrosa, which has proven to promote children's height growth. The aim of this study was to investigate the effects of HT042 on longitudinal bone growth, bone mass, and bone microstructure in growing rats using a high-resolution microcomputed tomography system. Four-week-old female rats were fed an HT042-containing diet for 2 weeks. Tibial length was measured at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Other studies found that adding astragalus extract mixture HT042 (Astragalus, Xanthium, and Acanthopanax senticosus ) stimulated epiphyseal plate cell proliferation, and induced IGF‐1 expression and longitudinal bone growth, which can help improve children's growth. HT042 increased longitudinal bone growth rate, improved trabecular bone quality, and improved bone strength and quality; moreover, it was proven to be safe as a growth agent for children's height, because toxicity was found in rats at an approximate lethal dose of >500 mg/kg, with no observed adverse reaction at 400 mg/kg/day (Kim et al, 2012; Song, Hyun, et al, 2017; Song, Lee, et al, 2017). It was also found that the production performance of laying hens could be improved by an appropriate amount of Chinese wolfberry, which also regulated lipid metabolism (Bai, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that adding astragalus extract mixture HT042 (Astragalus, Xanthium, and Acanthopanax senticosus ) stimulated epiphyseal plate cell proliferation, and induced IGF‐1 expression and longitudinal bone growth, which can help improve children's growth. HT042 increased longitudinal bone growth rate, improved trabecular bone quality, and improved bone strength and quality; moreover, it was proven to be safe as a growth agent for children's height, because toxicity was found in rats at an approximate lethal dose of >500 mg/kg, with no observed adverse reaction at 400 mg/kg/day (Kim et al, 2012; Song, Hyun, et al, 2017; Song, Lee, et al, 2017). It was also found that the production performance of laying hens could be improved by an appropriate amount of Chinese wolfberry, which also regulated lipid metabolism (Bai, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Phlomis umbrosa has the functions of detumescence, muscle growth, tendon continuation and bone grafting. It was found that the mixture of Phlomis umbrosa, Astragalus membranaceus and Acanthopanax senticosus could increase the longitudinal bone growth rate of growing rats, improve the quality of bone trabeculae, and enhance the microstructure of bone trabeculae and cortical bone during growth ( 138 ). Donghun Lee et al.used the extract of Phlomis gracile to treat female adolescent rats and found that it increased the longitudinal bone growth rate and promoted the proliferation and differentiation of chondrocytes by up-regulating the expression of local IGF-1 and BMP-2 in the growth plate ( 139 ).…”
Section: Therapeutic Strategies For Skeletal Growth Inhibition Caused...mentioning
confidence: 99%
“…Phlomis umbrosa Turczanimow (Family, Lamiaceae), is a medicinal plant, which has been used to treat allergic conditions [9], improve bone growth [10], and manage bonerelated diseases, such as OA and osteoporosis [11,12]. Another medicinal plant, Dipsacus asperoides C.Y.Cheng & T.M.Ai (Family, Caprifoliaceae) is used to treat broken bones and liver abnormalities [13].…”
Section: Introductionmentioning
confidence: 99%